Diabetic Retinopathy Screening: The First Telemedical Approach in an Italian Hospital. Issue 4 (July 2016) - Invernizzi, Alessandro; Bevilacqua, Maurizio T.; Cozzi, Mariano; Bianchi, Carlo; Pagani, Alessandro; Cigada, Mario; Staurenghi, Giovanni
Purpose: To assess the feasibility of a telemedical approach for diabetic retinopathy (DR) screening in the Italian population and to evaluate advantages/disadvantages in comparison to standard slit-lamp funduscopic examination (SFE). Methods: This 1-year, Italian, single-center, observational study evaluated semiautomatic fundus photography (FP) DR screening, performed during routine type 2 diabetes (T2D) systemic visits and examined remotely. Adults with T2D underwent SFE and 3-field FP. The study was divided into 2 stages (stage 1 validated the screening procedure, stage 2 evaluated the screening impact on the clinical practice). Annual costs of SFE ± FP screening were compared. Patients completed a DR screening questionnaire. Results: Of 1, 281 T2D patients enrolled, 61% were male (mean age 65.69 ± 12.64 years). In stage 1, 71% and 15% of patients were considered nongradable when FP was performed before (BPD) versus after pupil dilation (APD). The FP specificity was higher with APD vs BPD (79% vs 25%); therefore, FP APD only was used for stage 2. Of 1, 281 patients screened using FP APD, 240 (18.7%) had unreadable images; 64.3% did not have DR, and 17.0% were diagnosed with DR. There was a cost saving of €801.25 when screening was performed using FP. Overall, 98% of patients had a positive opinion of FP screening. Conclusions: The telemedicine approach provides a convenient, simple test that is well-received by patients and minimizes unnecessary referrals. Telemedicine may also reduce screening costs in our setting.